Some Help on the Way: Opportunistic Routing under Uncertainty - Horvitz, Eric; Krumm, John (2012)
We investigate opportunistic routing, centering on the recommendation of ideal diversions on trips to a primary destination when an unplanned waypoint, such as a rest stop or a refueling station, is desired. In the general case, an automated routing assistant may not know the driver’s final destination and may need to consider probabilities over destinations in identifying the ideal waypoint along with the revised route that includes the waypoint. We consider general principles of opportunistic routing and present the results of several studies with a corpus of real-world trips. Then, we describe how we can compute the expected value of asking a user about the primary destination so as to remove uncertainty about the goal and show how this measure can guide an automated system’s engagements with users when making recommendations for navigation and analogous settings in ubiquitous computing.
UbiComp 2012